Self-assembly of nanostructured proton exchange membranes for fuel cells - Tang, H.; Li, J.; Wang, Z.; Zhang, H.; Pan, M.; Jiang, San Ping (ACS Publications, 2013)
Research interest for the synthesis and fabrication of novel proton conducting electrolytes which can be operated under the elevated temperatures and low relative humidification (RH) conditions has been increased extensively in recent years. Self-assembly is a powerful, efficient and environment-friendly technical tool to create highly ordered nano-structures with unique properties and has been extensively investigated and applied to the development of highly efficient proton conductive electrolyte materials for fuel cells. For instance, nano-structured Nafion membranes via self-assembly approaches can achieve significantly enhanced proton conducitivity under reduced humidity, as compared to pristine Nafion membranes. In this Chapter, an overview of the application of self-assembly technique in the synthesis and development of novel nano-structured proton exchange membranes and their electrochemical performance for fuel cells is presented. New opportunities for highly ordered and low humidity or anhydrous-operating proton exchange membranes are critically reviewed and discussed.